PEDAGOGICAL USE OF DRAMATIC PERFORMANCE THROUGH SCIENCE SUBJECT FOR PEACE EDUCATION IN PARAGUAY - Martinez David; Diah Susanti; Ranti Kurniasih (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This research aims to change the effective learning process and encourage students to be more active and creative. As the main objective of MEC (2005), to educate students to become competent members of society as a product of one of the dimensions of science. Research focuses on drama as a method for teaching values and attitudes in education in Paraguay, where values and attitudes must be taught in science subjects because values and attitude are part of basic training every student and schools have a responsibility to achieve these goals as the main goal of the entire education system. Values and attitudes can be represented such as awareness-raising, tolerance, inclusion, and community sustainability. The studies analyzed relate to ways to make drama performances, as a pedagogic practice, that teachers can use in enlarging students’ science abilities such as student behavior and attitudes to become promoters of peace education. In this case, explicitly focusing on Dramatic Performance (DP) as a pedagogic tool to emphasize the teaching of values in science lessons. This study sees drama as an artistic expression that can be developed easily by teachers of various levels and can be applied in all subjects as a fun learning strategy. Through interviews, strong evidence is found that learning with drama helps teachers make the classroom more dynamic, fun, and participatory. In addition, this kind of method increases students’ curiosity, motivating them to participate actively in the learning process.